Penerapan Pengambilan Gambar Naturalistik Dalam Film Dokumenter “Jejak Rasa” - Shafa Najla Amira; Rinda Aunillah Sirait; Jimi Narotama Mahameruaji (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2026)
The development of audiovisual media in the digital era provides a significant opportunity for conveying information, particularly regarding social and cultural issues. One interesting phenomenon is the acculturation of Peranakan Chinese cuisine in Indonesia, which is currently becoming less well-known among the younger generation. This study aims to represent this acculturation process through a documentary film entitled "Jejak Rasa" (Traces of Taste), using a naturalistic visual approach. The method used is a qualitative approach with field observation, interviews, and documentation strategies, integrated with a community organizing process. The research subjects included Peranakan Chinese culinary practitioners in Bandung, such as culinary business owners and museum guides. The production process consisted of three main stages: pre-production, production, and post-production. The naturalistic approach was implemented through the use of predominantly eye-level camera angles, minimal camera movement, and the use of natural lighting to produce authentic visuals. The results of the study indicate that documentary films can be an effective medium for representing cultural values, history, and culinary identity as part of the acculturation process. Thus, this work serves not only as a medium of information but also as an effort to preserve culture relevant to the development of modern media.